Researching strategic alliances : emerging perspectives - Das, T. K. 1938- (Research in strategic alliances., 2010)
Researching Strategic Alliances: Emerging Perspectives is a volume in the book series Research in Strategic Alliances that will focus on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series will cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series will also include comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series will seek to disseminate theoretical insights and practical management information that will enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Researching Strategic Alliances: Emerging Perspectives contains contributions by leading scholars in the field of strategic alliance research. The nine chapters in this volume cover the topics of multilevel issues in strategic alliance research (Bo Bernhard Nielsen), alliances as sources of legitimacy (Paul M. Olk and Peter Smith Ring), alliance capability as an emerging theme (Ard-Pieter De Man, Geert Duysters, and Tina Saebi), trust and control in strategic alliances (Jeltje van der Meer-Kooistra and Ed Vosselman), pre-formation processes in interorganizational relations (Paul W. L. Vlaar, Elko Klijn, Africa Ariño, and Jeffrey J. Reuer), sequence of alliance ownership structure (Weilei (Stone) Shi and Akie Iriyama), the causes of joint venture termination (M. V. Shyam Kumar), alliance portfolio characteristics and organizational learning (Don Goeltz) and interpartner negotiations in the alliance development process (Rajesh Kumar and T. K. Das).